Hematological and histological changes from ingestion of Deepwater Horizon crude oil in zebra finches (Taeniopygia guttata). (1st December 2021) - Fallon, Jesse A.; Goodchild, Christopher; DuRant, Sarah E.; Cecere, Thomas; Sponenberg, D. Phillip; Hopkins, William A.
Abstract: Exposure to crude oil during spill events causes a variety of pathologic effects in birds, including oxidative injury to erythrocytes, which is characterized in some species by the formation of Heinz bodies and subsequent anemia. However, not all species appear to develop Heinz bodies or anemia when exposed to oil, and there are limited controlled experiments that use both light and electron microscopy to evaluate structural changes within erythrocytes following oil exposure. In this study, we orally dosed zebra finches ( Taeniopygia guttata ) with 3.3 or 10 mL/kg of artificially weathered Deepwater Horizon crude oil or 10 mL/kg of peanut oil (vehicle control) daily for 15 days. We found that birds receiving the highest dosage experienced a significant increase in reticulocyte percentage, mean corpuscular hemoglobin concentration, and liver mass, as well as inflammation of the gastrointestinal tract and lymphocyte proliferation in the spleen. However, we found no evidence of Heinz body formation based on both light and transmission electron microscopy. Although there was a tendency for packed cell volume and hemoglobin to decrease in birds from the high dose group compared to control and low dose groups, the changes were not statistically significant. Our results indicate that additional experimental dosing studies are needed to understand factors (e.g., dose- and species-specific sensitivity) and confounding variables (e.g., dispersants) that contribute to the presence and severity of anemia resulting from oil exposure in birds. Graphical abstract: Image 1 Highlights: Birds exposed to Deepwater Horizon crude oil had lower body weights and increased liver mass. Oil exposure increased reticulocytes and mean corpuscular hemoglobin concentration. Light and electron microscopy revealed no evidence of Heinz bodies in zebra finches exposed to oil.